2010
DOI: 10.1097/aln.0b013e3181f56029
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyethyl Starch 6% (130/0.4) Ameliorates Acute Lung Injury in Swine Hemorrhagic Shock

Abstract: Our study indicates that resuscitation after hemorrhagic shock with hydroxyethyl starch 130/0.4 led to less lung edema and less microvascular permeability in this swine model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
1
9
0
1
Order By: Relevance
“…Factors such as infection, 52 ventilator management, 43,53 fluid 21,54 and transfusion strategies 55 , and choice of volatile anesthetic, 56 may potentially impact the development and/or progression of ALI in the postoperative period. While the addition of such variables would be expected to improve the overall performance of our prediction model, their inclusion would preclude the use of this model as intended (preoperative risk assessment), prohibiting the identification of patients at high-risk of ALI prior to the surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as infection, 52 ventilator management, 43,53 fluid 21,54 and transfusion strategies 55 , and choice of volatile anesthetic, 56 may potentially impact the development and/or progression of ALI in the postoperative period. While the addition of such variables would be expected to improve the overall performance of our prediction model, their inclusion would preclude the use of this model as intended (preoperative risk assessment), prohibiting the identification of patients at high-risk of ALI prior to the surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Hemorrhagic shock was induced by retrieving units of blood from the central venous catheter targeting a mean arterial pressure (MAP) of 40 mmHg and/or a systemic lactatemia of C4 mmol/L. The shock phase (T1) was continued for 90 min after reaching the targets [8].…”
Section: Methodsmentioning
confidence: 99%
“…With little exception, results of these studies point consistently toward an anti‐inflammatory effect of HES. In a similar set of studies, the influence of HES on leukocyte function (activation, migration, and adhesion) assessed directly through histology, flow cytometry, and intravital fluorescence microscopy, or indirectly using different markers, demonstrated an overall decrease in activity of inflammatory cells in the presence of HES . In light of their experimental nature, and because of the controversial effects of suppression of inflammation in critically ill patients, the implication of these results for clinical practice must be assessed cautiously.…”
Section: Hes Exerts An Anti‐inflammatory Effectmentioning
confidence: 99%
“…The effect of HES on pulmonary permeability has been the subject of numerous experimental and clinical investigations, using clinical, laboratory, and histological methods to assess pulmonary vascular leakage and edema formation, including pulmonary leak index, extravascular lung water, lung injury scores, arterial blood gas analyses, and wet‐to‐dry lung ratios . Most of these studies reported a positive effect of HES in decreasing pulmonary permeability .…”
Section: Hes Has Pulmonary Protective Effectsmentioning
confidence: 99%